2012
DOI: 10.1111/j.1095-8649.2011.03211.x
|View full text |Cite
|
Sign up to set email alerts
|

An overview of the biology and status of undulate ray Raja undulata in the north‐east Atlantic Ocean

Abstract: The undulate ray Raja undulata is one of the lesser-known skates occurring on the continental shelf of the north-east Atlantic Ocean. It is patchily distributed throughout its range, with sites of local abundance in the central English Channel and off the coasts of Ireland, France, Spain and Portugal. Raja undulata is most abundant in coastal waters (<50 m deep) and is often found in proximity to large estuaries, rias and bays. It is a relatively large-bodied species, attaining a maximum total length (L(T) ) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 29 publications
1
19
0
Order By: Relevance
“…Many elasmobranch species also respond to local habitat characteristics such as substratum type [47], [48] and depth [49], [50]. In this context, it might be suggested that remaining (relatively) high biomass patches just reflect areas where high quality habitat supported greatest elasmobranch biomass prior to fishing.…”
Section: Discussionmentioning
confidence: 99%
“…Many elasmobranch species also respond to local habitat characteristics such as substratum type [47], [48] and depth [49], [50]. In this context, it might be suggested that remaining (relatively) high biomass patches just reflect areas where high quality habitat supported greatest elasmobranch biomass prior to fishing.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the complete absence of species of critical conservation concern may also reflect effective controls by the EU and efforts of fishermen and stakeholders to reduce landings of these groups. Perhaps a more stringent test of such action could be made in regions where threatened species are more locally abundant: e.g., R. undulata remains relatively common around the Channel Isles (Ellis, McCully & Brown, 2012), and analyses focused on this area could form a more rigorous test of effective landing controls. Interestingly, the largest growing species identified ( R. brachyura ) also occurred most frequently in the study.…”
Section: Resultsmentioning
confidence: 99%
“…The distribution of R. undulata in the north and central regions of mainland Portugal is in accordance with the other published data for south‐western Portugal (Baeta et al ., ), southern Portugal (Coelho et al ., ; Coelho & Erzini, ), Galicia (Bañon et al ., ), the U.K. (Ellis et al ., , ) and the Irish Sea (Minchin & Molloy, ). The occurrence of newborn and juveniles and egg‐laying females in estuarine habitats was also documented, proving their importance for the life cycle of the species.…”
Section: Discussionmentioning
confidence: 99%
“…According to Portuguese fishing records, R. undulata is relatively frequent off Setúbal and along the inshore waters off the Algarve coast (Coelho et al ., ; Baeta et al ., ). Inshore areas, namely estuaries and coastal lagoons, were identified as being associated with egg laying and as nursery sites (Prista et al ., ; Moura et al ., ; Ellis et al ., ).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation